The Relationship Between the Network of Non-coding RNAs-Molecular Targets and N6-Methyladenosine Modification in Colorectal Cancer - Lu, Senxu; Ding, Xiangyu; Wang, Yuanhe; Hu, Xiaoyun; Sun, Tong; Wei, Minjie; Wang, Xiaobin; Wu, Huizhe (Frontiers in Cell and Developmental Biology, 2021)
With the advancements in scientific research, non-coding RNA, including microRNA (miRNA), circular RNA (circRNA), and long non-coding RNA are gradually recognized as an indispensable part of biological processes. However, at present, the research is limited to the large-scale identification and characterization of the function of non-coding RNAs. Little is known about the interaction network of non-coding RNA. In this review, we collected recent publications (IF > 6) in the last quinquennium (2016-2020) for colorectal cancer (CRC) and a data-driven approach was adopted to establish direct and indirect interaction networks of non-coding RNAs. Based on this, we formally analyzed the sub-networks and the associations of m6A methylation with non-coding RNA as the core and coding genes as the supplement for CRC initiation and progression. Thus, this review presents the current core sub-networks of ncRNAs with the star target genes as well as their relationship with m6A methylation and emphasizes their critical roles in the development and chemical resistance for CRC treatment.